Development of novel HPMC edible coatings containing antifungal GRAS salts to control Alternaria black spot and preserve fruit quality of cold-stored “Rojo Brillante' persimmons - Fernández-Catalán, Asunción; Argente-Sanchis, Maricruz; Palou, Lluís; Pérez-Gago, María B. (2021)
Spain is the second producing country and the main exporter in the world of persimmons (Diospyros kaki Thunb.). Persimmon production is mainly based on the 'Rojo Brillante' cultivar. This cultivar has a short harvest period and the main challenge for the industry is to extend the fruit storage life, which requires effective methods to preserve fruit quality and control postharvest Alternaria black spot (ABS) caused by the pathogenic fungus Alternaria alternata. The objective of this work was to develop new Hydroxypropyl methylcellulose (HPMC)-lipid edible composite coatings containing selected food additives with antifungal properties effective to reduce the development of ABS on 'Rojo Brillante' persimmons artificially inoculated with the pathogen and preserve the quality of intact fruit during cold storage commercial conditions.